SIMULTANEOUS DETERMINATION OF HYDROCHLOROTHIAZIDE AND TELMISARTAN FROM PHARMACEUTICAL PREPARATIONS USING CAPILLARY ELECTROPHORESIS - STĂCESCU, Ștefana; HANCU, Gabriel; GAGYI, Laszlo; SOARE, Ruxandra Maria; KELEMEN, Hajnal (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Fixed-dose combinations of an angiotensin II receptor antagonist (telmisartan) and a thiazide diuretic (hydrochlorothiazide) provide an effective antihypertensive therapy while promoting patient compliance with the convenience of once-daily single dose administration. The current study investigated two capillary electrophoretic methods: a capillary zone electrophoresis (CZE) and micellar electrokinetic capillary chromatography one (MEKC) for the simultaneous determination of hydrochlorothiazide and telmisartan. In order to optimize the analytical conditions, efforts were focused on establishing the influence of several experimental parameters on the separation: buffer composition, concentration and pH, applied voltage, temperature, injection pressure and time. The separation of the two analytes can be achieved by CZE using a 25 mM phosphate buffer at pH 2.50 and by MEKC using a 50 mM borate buffer at pH 9.50 containing 25 mM sodium dodecyl sulfate as surfactant. The analytical performance of the two methods was verified in terms of their linearity, precision, accuracy and robustness, and the methods were applied for the determination of the analytes from fixed-dose combinations.